Administrative-Territorial Reform: The Experience of the Countries of Western Europe - Гаруст, Юрій Віталійович; Гаруст, Ю. В.; Гаруст, Юрий Витальевич; Harust, Yuriy V.; Дурнов, Євген Сергійович; Дурнов, Є. С.; Дурнов, Евгений Сергеевич; Durnov, Yevhen S.; Бойчук, Андрій Юрійович; Бойчук, А. Ю.; Бойчук, Андрей Юрьевич; Boichuk, Andrii Yu.; et al. (IEPDP – Facultad de Ciencias Jurídicas y Políticas - LUZ, 2020)
The relevance of this article is conditioned by the decentralization of the reform of political power in Ukraine, which presents the State with the permanent challenge of finding new ways to solve the problems of governance and governability at the district and regional level. The objective of the article was to carry out a scientific investigation on the mechanism of introduction of institutes of prefects in Ukraine, based on the experience of the main western European countries. The main research methods are general and specific, including the methods of logic, analysis and comparison of the sources consulted. The results of this study are to identify ways to introduce an institute of prefects in Ukraine. By way of conclusion, it highlights the importance of the results obtained, which is reflected in the fact that this study can serve as a basis to delineate future changes to the current legislation of Ukraine on issues of state administration, at the district and regional level, by introducing the institute of prefects.

Актуальність цієї статті зумовлена реформою ​​децентралізації політичної влади в Україні, яка ставить перед державою постійний виклик до пошуку нових шляхів вирішення проблем регулювання й управління на районному та регіональному рівнях. Метою статті було проведення наукового дослідження механізму впровадження інститутів префектів в Україні на основі досвіду основних західноєвропейських країн. Основні методи дослідження - загальні та конкретні, включаючи методи логіки, аналізу та порівняння використаних джерел. Результати цього дослідження полягають у визначенні шляхів запровадження інституту префектів в Україні. Як висновок, підкреслено важливість отриманих результатів, яка полягає в тому, що це дослідження може послужити основою для визначення майбутніх змін до чинного законодавства України з питань державного управління на районному та регіональному рівнях, в процесі запровадження інституту префектів.

Актуальность данной статьи обусловлена ​​реформой децентрализации политической власти в Украине, которая ставит перед государством постоянный вызов к поиску новых путей решения проблем регулирования и управления на районном и региональном уровнях. Целью статьи было проведение научного исследования механизма внедрения институтов префектов в Украине на основе опыта ключевых западноевропейских стран. Основные методы исследования - общие и конкретные, включая методы логики, анализа и сравнения использованных источников. Результаты этого исследования заключаются в определении путей внедрения института префектов в Украине. Как вывод, подчеркнута важность полученных результатов, которая заключается в том, что это исследование может послужить основой для определения будущих изменений в действующее законодательство Украины по вопросам государственного управления на районном и региональном уровнях, в процессе внедрения института префектов.
Harust Yu. Administrative-Territorial Reform: The Experience of the Countries of Western Europe / Yu. Harust, Ye. Durnov, A. Boichuk, O. Chernezhenko, I. Holosnichenko // Cuestiones Políticas. – V. 37 (65). – IEPDP – Facultad de Ciencias Jurídicas y Políticas - LUZ, 2020. – P. 249-268.
Keywords: institute of prefects in Ukraine; public service; public administration; decentralization of power; administrative-territorial reform; інститут префектів в Україні; державна служба; державне управління; децентралізація влади; адміністративно-територіальна реформа; институт префектов в Украине; государственная служба; государственное управление; децентрализация власти; административно-территориальная реформа; Research Subject Categories::LAW/JURISPRUDENCE